Influence of Foliar Application of Boron and Zinc on Growth, Reproductive Traits and Yield Performance of Green Gram (Vigna radiata L.) - Ankam, Shashank; Challam, Dawan Arkini; Shil, Sanjoy; Mondal, Subhasis; Nath, Rajib (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the pre-kharif seasons (March–May) of 2022 and 2023 at the District Seed Farm, AB Block, Kalyani Simanta, under Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India to evaluate the response of two green gram genotypes (TMB-37 and TMB-153). The experimental was designed in Factorial Randomized Block Design (FRBD) with nine different genotypes as treatments replicated thrice. The treatments were water spray as control, zinc at 30 µmol, zinc at 60 µmol, boron at 40 µmol, boron at 40 µmol+zinc at 30 µmol, boron at 40 µmol+zinc at 60 µmol, boron at 80 µmol, boron at 80 µmol+zinc at 30 µmol and boron at 80 µmol+zinc at 60 µmol. Although the genotypes differed significantly in several yield-attributing traits, their final grain yield was statistically similar, indicating yield stability of genotypes. Boron application significantly enhanced floral frequency, flower-to-pod transition, pods plant-1, seeds pod-1, pod weight, seed weight plant-1 and grain yield, with the lower dose (40 µmol) proving sufficient and economical. Zinc application also improved most yield components and yield, with optimal response at 30 µmol, while floral frequency and 100-seed weight showed limited sensitivity. Interaction effects were largely non-significant, except for pod weight and yield, where the combined application of boron (40 µmol) and zinc (30 µmol) produced superior performance.